Intergenerational transmission of skills during childhood and optimal public policy - Alessandra Casarico; Luca Micheletto; Alessandro Sommacal (Center for Economic Studies and ifo Institute (CESifo), 2011)
The paper characterizes the optimal tax policy and the optimal quality of day care services in a OLG model with warm-glow altruism where parental choices over child care arrangements affect the probability that the child becomes a high-skilled adult in a type-specific way. With respect to previous contributions, optimal tax formulas include type-specific Pigouvian terms which correct for the intergenerational externality in human capital accumulation. Our numerical simulations suggest that a public policy that disregards the effects of parental time on children's human capital entails a welfare loss that ranges from 0:2% to 5:7% of aggregate consumption.
Keywords: H21; H23; J13; J22; J24; 330; optimal taxation; day care quality; intergenerational transmission of skills; early childhood environment; warm-glow; Optimale Besteuerung; Kinderbetreuung; Dienstleistungsqualität; Generationenbeziehungen; Qualifikation; Familienökonomik; Overlapping Generations; Theorie